A Review of the Chinese National Center for Science and Technology Evaluation - Laura Pan Luo (The Evaluation Center at Western Michigan University, 2005)
China is now in a transitioning stage from planned economy to market economy. There is a growing interest in China to have a strong evaluation process in place so that planning and decisions can be based on valid and credible information. Evaluation also provides a guide for resource allocation.